Constructing Foucault's ethics A poststructuralist moral theory for the twenty-first century. - Olssen, Mark (Book collections on Project MUSE., 2021)
The work of Michel Foucault has had a huge influence on contemporary philosophy, but one thing it lacks is a normative ethical framework. Seeking to construct an ethics consistent with Foucault's core postulates, this study advances the concept of 'life continuance', an approach it contrasts with a range of other, established systems.